Protection and Liberalization : A Review of Analytical Issues - Corden, W. (Occasional Papers; Occasional Paper ;, 1987)
This paper deals with trade policy issues of particular interest to the Fund. It is motivated both by the revival of protectionist attitudes in the industrial countries and the prevalence of liberalization proposals for developing countries. In veiw of Fund concerns with the functioning of the International monetary system and with the individual countries' macroeconomic policy, and especially exchange rate issues, relate to protection.